2008
DOI: 10.1007/s11103-008-9390-9
|View full text |Cite
|
Sign up to set email alerts
|

Alternative transcription initiation of the nitrilase gene (BrNIT2) caused by infection with Plasmodiophora brassicae Woron. in Chinese cabbage (Brassica rapa L.)

Abstract: In clubroot disease, gall formation is induced by infection with the obligate biotroph Plasmodiophora brassicae, and cell hypertrophy is dependent on increased auxin levels. The enzyme nitrilase is suggested to play an important role in auxin biosynthesis in plants. Here, we investigated the expression of nitrilase genes in clubroot disease in Chinese cabbage (Brassica rapa L.). We isolated four isogenes of nitrilase (BrNIT1, BrNIT2, BrNIT3, and BrNIT4) from Chinese cabbage. When a BrNIT2-specific probe was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…In Hornet galls, NIT1 transcription was up-regulated 35 dai, and especially at 49 dai (Figure 7). Our data are in accordance with several reports that describe the up-regulation of transcription of nitrilase isoforms in clubroot tissues compared to controls in different host plants such as Brassica rapa (turnip [29], Chinese cabbage [30]), or Brassica juncea [31], and specific expression of nitrilase 1 and 2 genes in developing galls of Arabidopsis thaliana , as well as with the up-regulation of myrosinases and glucosinolate metabolism [13,32,33]. The difference between IAA levels and the expression of IAA-biosynthetic genes may be given by the up-regulation of the expression of GH3 genes (encoding auxin conjugating enzymes), as was shown in the case of Arabidopsis thaliana [26].…”
Section: Discussionsupporting
confidence: 93%
“…In Hornet galls, NIT1 transcription was up-regulated 35 dai, and especially at 49 dai (Figure 7). Our data are in accordance with several reports that describe the up-regulation of transcription of nitrilase isoforms in clubroot tissues compared to controls in different host plants such as Brassica rapa (turnip [29], Chinese cabbage [30]), or Brassica juncea [31], and specific expression of nitrilase 1 and 2 genes in developing galls of Arabidopsis thaliana , as well as with the up-regulation of myrosinases and glucosinolate metabolism [13,32,33]. The difference between IAA levels and the expression of IAA-biosynthetic genes may be given by the up-regulation of the expression of GH3 genes (encoding auxin conjugating enzymes), as was shown in the case of Arabidopsis thaliana [26].…”
Section: Discussionsupporting
confidence: 93%
“…In Arabidopsis, genes involved in auxin synthesis, transport, and responses are strongly upregulated. Regulation of nitrilase genes involved in auxin synthesis has also been reported in B. rapa (Ando et al 2008). The alh1 mutant of Arabidopsis, which may be affected in auxin transport, shows resistance responses to P. brassicae (Devos et al 2006).…”
Section: Phytohormones Regulating Development and Defense May Controlmentioning
confidence: 80%
“…rapa ssp. pekinensis Isolate Ibaraki-1 Roots 10, 20, 25, 30, 35 and 40 dpi Expression analysis of nitrilase genes ( BrNIT2 ) suggested that 1.1 kb transcripts might be involved in auxin overproduction during clubroot development [ 237 ] B . rapa ssp.…”
Section: Transcriptomicsmentioning
confidence: 99%